Etiologic Profile of Older Children With Diffuse Radiological Changes in Eastern China - Xu, Xuefeng; Liu, Lingke; Xu, Xuchen; Ma, Qian; Teng, Liping; Zhou, Haichun; Yang, Li; Lu, Meiping (Frontiers in Pediatrics, 2022)
Objective: To analyze the etiology of chest diffuse radiological changes (DRC) in children older than 2 years. Methods A retrospective study was conducted on a primary cohort of children with DRC underwent high resolution computed tomography (HRCT). Results DRC mainly included bronchial wall thickening, interlobular septal thickening, pleural thickening, ground glass opacity, mosaic perfusion, reticular & linear opacities, nodular opacity, and tree-in-bud. Of the identified 457 children with DRC, 83 of children older than 2 years with DRC were included in the present study. Ground glass opacity (53, 63.9%) and reticular & linear opacities (44, 53.0%) were frequently identified findings of HRCT, and no tree-in-bud pattern was observed. By contrast, among children with DRC by M. pneumoniae (n = 64), bronchial wall thickening (33, 51.6%), and mosaic perfusion (17, 26.6%) were common patterns of HRCT in addition to ground glass opacity (36, 56.3%). Most of etiologies were connective tissue disease (24, 28.9%), followed by diffuse alveolar hemorrhage syndrome (9, 10.8%), Langerhans cell histiocytosis (7, 8.4%), and recurrent aspiration (6, 7.2%). Conclusions This study adds further insights into the role of HRCT in diagnosing childhood interstitial lung diseases, indirectly reflecting disease compositions.